1994
DOI: 10.1016/0378-1097(94)90162-7
|View full text |Cite
|
Sign up to set email alerts
|

Pectolytic enzymes produced by Pseudomonas syringae pv. glycinea

Abstract: Six strains of Pseudomonas syringae pv. glycinea secreted, in vitro, the pectolytic enzymes pectate lyase (PL) and polygalacturonase (PG). All six bacterial strains were capable of producing both enzymes, but at different levels. Strain NCPPB 2411 secreted a large amount of PG and the highest level of PL. Both enzymes exhibited temperature optima between 30 and 40°C. PL exhibited a pH optimum at 8.0, while the pH optimum of PG was 5.0. For maximum activity PL required Ca2+. Upon isoelectrofocusing (IEF), the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…Enzymes that are active at low temperatures are especially desirable for such degradation processes and would enable low energy treatment. Cold‐adapted PL producers described so far are predominantly bacterial representatives of a number of genera (Magro et al. 1994; Laurent et al .…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes that are active at low temperatures are especially desirable for such degradation processes and would enable low energy treatment. Cold‐adapted PL producers described so far are predominantly bacterial representatives of a number of genera (Magro et al. 1994; Laurent et al .…”
Section: Introductionmentioning
confidence: 99%
“…lycopersici (Jones et al, 1972;Lafitte et al, 1984;Powell et al, 2000). These proteins also have been found in the secretome of Arabidopsis roots when the plant is infected with P. syringae (Magro et al, 1994;De-la-Peña et al, 2008), which indicates that PGIPs participate in defense response signaling in the rhizosphere during bacterial attack. Therefore, PGIPs could be exploited as a strategy for protecting crops against PG-producing pathogens.…”
Section: Pgsmentioning
confidence: 83%
“…PGs are one of the factors responsible for causing severe diseases in many plants (Collmer and Keen, 1986;Magro et al, 1994;Shieh et al, 1997;Aysan et al, 2003). For instance, Aspergillus flavus, a saprophytic fungus responsible for important losses in maize, peanut (Arachis hypogaea), and cotton (Lillehoj et al, 1974;Shieh et al, 1997;Asis et al, 2005), produces a PG, P2c, which causes intercarpellary membrane damage due to the loss of pectin integrity, thus helping the spread and invasion of the fungus (Shieh et al, 1997).…”
Section: Pgsmentioning
confidence: 99%
“…These are comparable with those of Bacillus sp. KSM-P15, having optimal activity around pH 10.5 and 50–55°C [18], and superior to several alkaline pectinases reported by Nasuno and Starr [19], Davé and Vaughn [20], and Magro et al [21], exhibiting the maximum activity at pH 8.5 and 45°C, and pH 8.0–8.5 and 60°C, pH 8.0 and 30–40°C, respectively. The PGL was stable at pH 7.0–10.5 and 30–50°C, and at least 81% of its maximum activity was retained within 8 h. These also showed that it was suitable for degumming ramie.…”
Section: Discussionmentioning
confidence: 99%